Demonstration of the kidney functions obtained from a cadaveric donor in a rat model by the dynamic renal scintigraphy - Mitil, H.; Koc, Z.; Guzel, Y.; Kom, M.; Ozer, A.; Ozercan, H.; Balci, T. (Springer, 2013)
[Abstract Not Available]
Annual Congress of the European-Association-of-Nuclear-Medicine (EANM) -- OCT 19-23, 2013 -- Lyon, FRANCE
Keywords: Brain death; Tc 99m DTPA; renal functions